Point-of-Care Ultrasound (POCUS) and Epsilon wave - Ky, Wong Choc; Fauzi, Mohd Hashairi; Rahman, Andey; Mohd Shukri, Mohd Faiz; Tuan Kamauzaman, Tuan Hairulnizam; Abdul Ghani, Mohd Najib (International Journal of Human and Health Sciences (IJHHS), 2022)
Arrhythmogenic right ventricular cardiomyopathy (ARVC) is often underdiagnosed in ruling out the cardiac cause for any syncope. It is an inherited cardiomyopathy characterized by fibro-fatty replacement of right ventricular myocardium. ARVC is the second most common cause of sudden cardiac death (SCD) after hypertrophic obstructive cardiomyopathy (HOCM), causing up to 20% of SCD in younger patients (age <35 yo). The prevalence is 1:5000 people overall. We described a case report of suspected ARVC and the role of bedside electrocardiography (ECG) and point-of-care ultrasound (POCUS) in Emergency Department. International Journal of Human and Health Sciences Vol. 06 No. 01 January’22 Page: 136-139